An Offline Corpus for Legal Translations into Italian: a Case Study with a Land Lease Agreement (Altre Modernità, 2020)
Offline corpora are claimed to be helpful in technical translations. This paper explores whether a corpus of Italian land lease agreement samples and the civil code can be supportive in legal translations. To this end, three experienced translators were involved in a trial lesson and assigned to translate a land lease agreement from English (L2) into Italian (L1). They participated in a webinar where they became acquainted with corpus compilation and analysis. During the training, they clarified linguistic doubts, had the possibility to verify attested usage of words, and they could identify collocational preferences as well as word frequencies. Thanks to the corpus analysis, the translators could improve the quality of their translation work and learn new terminology. The only drawback of using an offline corpus was perceived as lying in its time-consuming compilation and in the fact that in order to be representative, a corpus must be composed of a certain amount of reliable documents.